'One Stop Prostate Clinic': prospective analysis of 1000 men attending a public same‐day prostate cancer assessment and/or diagnostic clinic. Issue 4 (25th September 2020) - Hawks, Cynthia; Moe, Andrew; McCombie, Steve; Hamid, Akhlil; Brown, Matthew; Hayne, Dickon
Abstract : The One Stop Prostate Clinic – same‐day assessment and/or prostate cancer diagnostic clinic – was reported in this study. Abstract: Background: This study reported the outcomes of the first 1000 men to attend the One Stop Prostate Clinic, a consultant‐led same‐day prostate cancer assessment and diagnostic clinic at a tertiary public hospital. Methods: Prospective audit of demographic and clinical data between August 2011 and November 2017 was conducted for same‐day urological assessment and/or trans‐rectal ultrasound (TRUS)‐guided prostate biopsies with peri‐prostatic infiltration local anaesthetic (PILA) and antibiotic prophylaxis. Results: A total of 466 (47%) rural and 534 (53%) metropolitan men attended. Rural mean (range) age was 63 years (38–86) and 65 years (37–89) for metro men ( P = 0.006). Rural median (range) prostate specific antigen (PSA) level was 6.7 g/mL (0.2–450) and 7.3 ng/mL (0.5–860) for metro men ( P = 0.011). Twenty‐five men (2.5%) refused/could not tolerate TRUS‐guided biopsy using PILA. One hundred and fifty‐one (15%) men had multi‐parametric magnetic resonance imaging prior to TRUS biopsy and 876 (88%) men had prostate biopsies, with a new cancer diagnostic rate of 51% (443 men). Clinically significant prostate cancer was detected in 339 (34%) men. The overall infective complication rate requiring hospital admission rose from 1.4% to 2.9% after the prophylactic antibiotic regimen changed from six doses of 500 mg ciprofloxacin to a single dose of 500 mg ( P = 0.398). Conclusion: This is the largest single institution prospective TRUS prostate biopsy series in Australasia. Biopsies using PILA were well tolerated with low complication rates and diagnosed a high rate of clinically significant prostate cancer. The 'One Stop' pathway generates efficiencies with combined assessment and diagnostic process, lessens demand on outpatient clinic appointments and reduces travel time and costs for rural men.